1981
DOI: 10.1111/j.1464-410x.1981.tb03151.x
|View full text |Cite
|
Sign up to set email alerts
|

Elastin and Collagen in the Normal and Obstructed Urinary Bladder

Abstract: Histological and chemical studies were carried out on the elastin and collagen content of the normal and the obstructed urinary bladder wall. The observations were made on 3 different age groups: (1) 3-month-old children with vesical outlet obstruction, (2) children aged between 4 and 8 years with partial vesical obstruction, and (3) adults with a chronically obstructed bladder. An increase in elastic tissue was shown only in the newborn and in the adults. The collagen did not vary in any of the cases studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 7 publications
5
29
0
2
Order By: Relevance
“…electronic microscopy (6,14). In the bladder of patients without urologic disease, muscle fibers are grouped with few connective tissue between their bundles.…”
Section: A B C Dmentioning
confidence: 99%
See 2 more Smart Citations
“…electronic microscopy (6,14). In the bladder of patients without urologic disease, muscle fibers are grouped with few connective tissue between their bundles.…”
Section: A B C Dmentioning
confidence: 99%
“…Cortivo et al (6) evaluated the connective tissue of bladders of normal patients and patients with infravesical obstruction. Three distinct groups were assessed: 1) 3-month children with infravesical obstruction, 2) children between 4 to 8 years with partial infravesical obstruction and 3) adults with chronic infravesical obstruction.…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The plate was sealed and incubated for 45 mins at 65 o C. Absorbance at 540 nm was read on a Labsystems Multiskan® Multisoft microplate reader (Labsystems, Helsinki, Finland). A multiplication factor of 7.2 was used to convert total hydroxyproline to total collagen (Cortivo et al, 1981).…”
Section: Determination Of Total Collagen Productionmentioning
confidence: 99%
“…Many studies demonstrated that in BOO there is recruitment of neural-detrusor responses causing altered neural control of micturition resulting in reduced bladder contractility, impaired central processing, and altered sensation [28][29][30][31][32]. Gosling et al [9] in a prospective study showed that BOO leads to decrease in the autonomic innervations of human DM which in turn results in decrease sensitivity of bladder.…”
Section: Neurological Diseasementioning
confidence: 99%